A review on the legislative aspect of artificial fruit ripening. Issue 1 (December 2016) - Islam, Md.; Mursalat, Mehnaz; Khan, Mohidus
Abstract Fruit ripening is a natural process in which a fruit goes through various physical and chemical changes and gradually becomes sweet, colored, soft, and palatable. Fruit ripening process can also be stimulated by applying artificial fruit ripening agents. Farmers and vendors often use artificial ripening agents to control the rate of fruit ripening. However, because of the potential health hazards related to the ripening agents, artificial fruit ripening process is highly debatable throughout the world. There are existing laws and guidelines to control artificial fruit ripening process. This article highlights the legal aspects of artificial fruit ripening and fruit adulteration throughout the world. Different laws and acts of both the developed and developing countries to control and prohibit artificial fruit ripening and adulteration using hazardous chemicals are discussed here. The technical and economic issues related to artificial fruit ripening are also addressed in this study. This article aims at developing awareness among government agencies, policymakers, farmers, vendors, and scientists, as since it will take collective participation of different stakeholders to address different aspects of artificial fruit ripening issues and to provide an effective solution.